EFFECT OF LAND CONFIGURATION AND DIFFERENT ORGANIC SOURCES ON GROWTH, YIELD AND QUALITY OF CARROT UNDER ORGANIC FARMING - B. SOLANKI; A. R. KASWALA; P.K. DUBEY; A.P. ITALIYA (The Bioscan, 2020)
A field experiment was conducted at the certified organic farm, Navsari Agricultural University, Navsari during Rabi season of 2017-2018 to study the effect of land configuration, fertilizer level and liquid formulation on growth, yield and quality of carrot under organic farming. The treatments imposed were three levels of land configuration i.e. C 1 : Flatbed C 2 : Ridge and furrow and C 3 : Broad bed, three levels of fertilizer i.e. F 1 : 100% N through vermicompost F 2 : 75% N through vermicompost, and F 3 : 50% N through vermicompost and two levels of liquid formulation i.e. L 1 : Jeevamrut and L 2 : Amritpani in FRBD which replicated thrice. Overall the growth, yield attributes, yield and quality parameters were significantly highest with individual treatments C 3 , F 1 and L 1 in all the cases. Significantly maximum root yield of carrot was achieved when 75% N was supplied in broad bed which was at par with 100% N application in all the treatments of land configuration. However root volume, root girth and root length was also affected significantly with the interaction effect of CxF and FxL. Further CxF interaction was also significant with shoot length while FxL interaction was found significant with quality parameters i.e. carotene and TSS content.